Utilization of waste tyre rubber and carbon black to develop a neoprene rubber hybrid composite. (2020) - Kaliyappan, P.; Dhananchezian, M.; Rajkumar, K.
Abstract: This study aims to develop Natural-Neoprene rubber hybrid composite using different fillers of natural waste tyre rubber and carbon black. This study includes the effect of varying the carbon black on the morphological and mechanical properties of fabricated composite. Four formulation were trialed by natural rubber (95, 90, 85, 80 phr), neoprene rubber (5, 10, 15, 20 phr) based hybrid rubber composites with waste tyre rubber particles (5, 10, 15, 20 phr) and carbon black (10, 20, 30, 40 phr), and nylon fiber and silica were fixed at 10 and 20 phr respectively. Hybrid rubber composite was synthesized by two roll mill and then hydraulically pressed. Among the developed Natural-Neoprene rubber hybrid composites, the compound of 80/20 phr Natural-Neoprene rubber, 20 phr waste tyre rubber and 40 phr carbon black showed peak mechanical properties over the others.